PALMITOYLETHANOLAMIDE (PEA) IN NEUROLOGY: MECHANISMS, CLINICAL APPLICATIONS, AND THERAPEUTIC PERSPECTIVES - Jakub Przerwa (International Journal of Innovative Technologies in Social Science, 2025)
Palmitoylethanolamide (PEA) is a fatty acid amide with anti-inflammatory and neuroprotective properties that acts on the endocannabinoid system and represents a potential therapeutic agent in neurological disorders as well as conditions accompanied by chronic and neuropathic pain. Numerous studies indicate that PEA plays a key role in modulating the neuroinflammatory response through the ALIA mechanism and activation of the PPAR-α receptor, thereby regulating mast cells, microglia, and astrocytes (1). These properties lead to reductions in neuropathic pain, inhibition of neurodegeneration, and improvements in neuronal function in various inflammation-related disorders. In recent years, the efficacy of ultramicronized PEA has been demonstrated in the treatment of chronic pain, neuralgia, migraine, and sciatica (2). However, large randomized clinical trials are still required to confirm its use in neurodegenerative diseases such as Alzheimer’s disease, Parkinson’s disease, and multiple sclerosis.This article presents the current state of knowledge on PEA, its pharmacological properties, mechanisms of action, and potential therapeutic applications. Particular emphasis is placed on the innovative nature of PEA as an inexpensive, well-tolerated adjuvant therapy with significant potential in neurology.